Adolescents' depressive moods and parents' family-work interaction - Lu, Li (Frontiers in Public Health, 2023)
Introduction For working parents with dependent children, parenthood is essential to their “life” component, which could profoundly influence their work experiences. Since depressive moods rise sharply in adolescence, this study aims to investigate the relationship between children's depressive moods and parental family-work interaction. Integrating the literature on emotions and family-work interaction, I propose that adolescents' depressive moods (over the past 2 weeks) decrease parents' work engagement via increased parents' family-work conflict. Further, I hypothesize that adolescent performance-avoidance, a key trait related to adolescents' long-term emotional experiences, moderates the indirect relationship. Methods Using a multiple-source, time-lagged design, I tested hypotheses using data collected from 468 adolescent-parent dyadic from China. Results I found that adolescents' depressive moods relate negatively to their parents' work engagement via increased parents' family-work conflict when adolescents have low levels of performance-avoidance. When an adolescent has a high level of performance-avoidance, parents show a relatively higher degree of family-work conflict and lower work engagement regardless of adolescents' depressive moods. Discussion I discuss the theoretical and practical implications for employee family-work interaction and work engagement.